THE URGENCY OF FORMING AUCTION LAW TO SUPPORT LEGAL CERTAINTY FOR AUCTION OFFICIALS THROUGH ONLINE AUCTIONS - Ulisy Syarifati; Rahmatul Hidayati (SOSIOEDUKASI, 2026)
Analyzing the regulatory urgency and determining the composition of technology-adaptive material content constitute the objectives of this research. The study applies a normative juridical method, supported by a statutory and conceptual framework. The research results show that: 1) The establishment of a national Auction Law is urgently needed to address the dualism of regulations. Currently, the main basis for auctions is the Vendu Reglement, a Dutch colonial legacy regulation that regulates general sales procedures and has been in effect since April 1, 1908. Hierarchically, the Vendu Reglement has the same status as a Law based on the Transitional Provisions of the 1945 Constitution. Conflicts arise because online auction procedures are only regulated at the level of the Minister of Finance Regulation, which is hierarchically lower, so that based on the principle of Lex superior derogat legi inferiori, the regulation is vulnerable to being revoked because it is considered to deviate from the physical obligations in the Vendu Reglement. 2) National codification is needed as a basis for legal certainty and protection for Auction Officials. The formulation of the material must include a redefinition of “reading” minutes digitally, the legality of electronic signatures that are equivalent to authentic deeds, and limitations on officials’ responsibility for electronic system failures.